2016
DOI: 10.1021/acs.cgd.5b01341
|View full text |Cite
|
Sign up to set email alerts
|

Supersaturation Potential of Salt, Co-Crystal, and Amorphous Forms of a Model Weak Base

Abstract: High energy solids, such as salts, co-crystals, or amorphous solid dispersions, have been widely used to generate supersaturated aqueous solutions and improve drug bioavailability. However, most research on solubility enhancing strategies has focused on the kinetics of dissolution, and there is relatively little comparison of the different degrees of supersaturation achieved by using different solid state forms of the same compound. Recent studies from our group have demonstrated that the maximum achievable su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…Studies have found that solutions generated from drugs with API in salt forms can be maintained at supersaturation with addition of a polymeric crystallization inhibitor to the formulation. 29 Thus, a "spring parachute" effect can be created inside GI tract with this salt being a "spring" to achieve initial supersaturation and the crystallization inhibitor being a "parachute" to maintain the solution at a supersaturated level. 30,31 In contrast, increased solubility in gastric environment would not be anticipated if the besylate salt should be selected as the development solid form for compound A.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that solutions generated from drugs with API in salt forms can be maintained at supersaturation with addition of a polymeric crystallization inhibitor to the formulation. 29 Thus, a "spring parachute" effect can be created inside GI tract with this salt being a "spring" to achieve initial supersaturation and the crystallization inhibitor being a "parachute" to maintain the solution at a supersaturated level. 30,31 In contrast, increased solubility in gastric environment would not be anticipated if the besylate salt should be selected as the development solid form for compound A.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this former behavior, cocrystals are potential candidates for the development of supersaturating drug delivery systems [20,21]. A strategy to control cocrystal dissolution, drug supersaturation and precipitation is the use of supersaturated formulations, which incorporates additives and excipients such as cyclodextrins, surfactants and polymers [22].…”
Section: Introductionmentioning
confidence: 99%
“…The drug concentration of the water-rich phase corresponds to the amorphous solubility of the drug while the excess drug precipitates forming a dispersed, colloidal (nano-droplets) amorphous drug-rich phase (Indulkar et al, 2016;Sun et al, 2016). LLPS thus typically occurs under the following conditions: (i) in the presence of precipitation inhibitors, (ii) with weakly basic compounds when the pH of the solution is increased and (iii) upon dissolution of salts (Almeida e Sousa et al, 2016;Indulkar et al, 2015). After LLPS, the solution is still supersaturated with respect to the equilibrium solubility of the stable crystal form and crystallization will eventually occur at some time point (Fig.…”
Section: Supersaturating Drug Delivery Systemsmentioning
confidence: 99%